The Dietary Sugars Intake: The Role In Alzheimer’s Disease Pathomechanism - Rifka Wangiana Yulia Putri; Dwi Pratika Anjarwati; Damar Mashkhun Rizqi (Clinical and Research Journal in Internal Medicine, 2023)
Alzheimer’s disease is a common neurodegenerative disease that affect elderly and it became a serious global burden for years. Despite many studies have been performed, an effective cure for Alzheimer’s was still not be found. Therefore, it is necessary to not only focus on curative methods but also preventive methods with modifiable risk factors and underlying disease, for example lifestyle and metabolic disease, as potential approach in Alzheimer’s disease prevention in the future. The excessive dietary sugar intake has been suggested as a risk factor of many diseases such as metabolic disease and cognitive impairment disease. It may promote cognitive declines through some pathways such as induce alteration of gut microbiomes, metabolism and immune system. These abnormal processes may evoke amyloid β plaque formation and neurofibrillary tangles in brain cells as the effect of chronic inflammation. Chronic inflammation has been widely studied as the hallmark of Alzheimer’s disease pathology. Therefore, the correlation between dietary sugar and impairment cognitive, specifically Alzheimer’s disease will be summarized.